Cookies for hypertension patients - Herawati, Nurul; Kumorowulan, Suryati; Djamil, Masrifan (MEDISAINS, 2022)
Background: Papaya and celery leaves are usually consumed as cooked vegetables and have a bitter taste and distinctive aroma. The flavonoid antioxidants in papaya and celery can increase the dilation of blood vessels, thereby possibly lowering blood pressure. They have been made to make cookies easy to enjoy and liked by hypertensive patients.Objective: Making and testing papaya combined celery leaf cookies to control blood pressure in hypertensive patients.Methods: This is a true experimental pretest-posttest with a control group design. The respondents are 34 women of reproductive age who have hypertension, divided into 17 respondents in the treatment group and 17 respondents in the control group. The cookies are made from papaya and celery leaves, and 5 mg of Amlodipine are given every day (for two weeks). Furthermore, blood pressures are measured on days 1, 5, 10, and 15.Results: Hypertension patients consuming papaya combined celery leaf cookies and amlodipine 5 mg had lower blood pressure than those consuming only 5 mg amlodipine (p<0.05).Conclusion: Papaya leaf cookies with a combination of celery are suitable for consumption by hypertensive patients because they can lower blood pressure.